Risk Factors Predictive of Recurrence and Progression for Patients Who Suffered Initial Recurrence After Transurethral Resection of Stage pT1 Bladder Tumor in Chinese Population: A Retrospective Study. Issue 5 (February 2016) - Shen, Zhonghua; Xie, Linguo; Chen, Tao; Tian, Dawei; Liu, xiaoteng; Xu, Hao; Zhang, Yu; Wu, Zhouliang; Sha, Nan; Xing, Chen; Ding, Na; Hu, Hailong; et al.
Abstract : Abstract: Bladder cancer is one of the most common malignancies worldwide and the stage pT1nonmuscle invasive bladder cancer (NMIBC) has a high probability of recurrence after initial diagnosis and treatment. However, risk factors predictive of repeated recurrence and progression of pT1 bladder tumors after primary relapse have not been uncovered. Thus, we conducted the retrospective study. A total of 418 patients who suffered initial recurrence after transurethral resection (TUR) of pT1 bladder tumor were selected for the analyses. Clinic information of the patients was retrieved from their medical records. Recurrence-free survival (RFS) and progression-free survival (PFS) were estimated using the Kaplan–Meier method. Univariate and multivariate analyses were performed using a Cox proportional hazards regression model. The probability of recurrence and progression by multivariate analyses was used as a surrogate marker to construct receiver operating curve (ROC). Results showed that variables including time to prior recurrence time, prior treatment, number of tumor, tumor size, tumor grade, and time of instillation after surgery were associated with the repeated recurrence of pT1 bladder tumor ( P  < 0.05). The variables including time to prior recurrence time, tumor size, tumor grade, carcinoma in situ (CIS), and time of instillation after surgery were associated with progression of pT1 bladder tumor ( P  < 0.05). In the present study, the multivariate model showed an area under ROC (AUC) value of 0.754 and 0.798 for tumor recurrence and progression, respectively, which was more effective in prediction than a single risk factor. In conclusion, we have identified several risk factors relevant to RFS and PFS for patients who have had a history of recurrence of pT1 bladder tumor after TUR. These predictive factors may help urologists to stratify patients into distinct risk groups of recurrence and progression, which probably contributes to the individualized treatment for patients.